阻尼对高速凸轮机构动力学的影响分析 - 田亚平; 康军凤 (Jixie chuandong)
Considered the factor of damping,a single degree of freedom’s dynamic model of the high-speed cam mechanism is established.Choosing the law of sine acceleration motion as the excitation function,a displacement and acceleration dynamic response equations of the main vibration phase and residual vibration phase,the working dynamic response change curve through the inferential reasoning working end movement equation is derived.The result is obtained that different period and damping ratio have different impact on dynamic response to the main vibration phase and residual vibration phase.It provides the theory foundation for high-speed cam mechanism’s rational design.